Corrosion behavior of Mg-Zn-Ca amorphous alloys with Nd addition in simulated body fluids - Qin Chunling; Xiao Tongna; Li Yongyan (China Foundry, 2014)
The effects of Nd addition on corrosion behavior of Mg66Zn30Ca4 amorphous alloys in simulated body fluids (SBF) were studied in this paper. Electrochemical properties of the samples before and after corrosion were determined. Surface morphologies of samples after immersion in SBF at 37 篊 for different times were observed under scanning electron microscope (SEM). Results show that the corrosion resistance of Mg-based alloys in SBF is improved with the addition of Nd element. The electrochemical properties indicate that microalloying Nd element to the alloys leads to an ennoblement in the open circuit potentials of the alloys and a decrease in the anodic current density in SBF, especially for the Mg66-xZn30Ca4Ndx alloys with Nd content of 1.0at.%-1.5at.%. It was observed that the surface morphologies of the alloys immersed in SBF change with the Nd addition. A flake-like structure parallel to the alloy substrate formed on the surface of 1.0at.% Nd-containing alloy immersed in SBF for 7 days improves the corrosion resistance of the amorphous alloys by blocking the corrosion liquid from attacking the alloys.